Toward an Afric-ecological education: an alternative strategy for the development of Sub-Saharan African countries - Keita, Fatoumata (Ciência & Trópico, 2013)
ABSTRACT The purpose of this article is to discuss the paramount necessity to implement an adequate educational system in order to achieve sustainable development in the SSA countries with a focus in Mali, one of the poorest countries in the world with an endemic educational crisis. It is a truism that education is the cornerstone of development. In this respect, any strategy of development in SSA shall start with a change in the pedagogy. This reform implies not only a rethinking of knowledge production and teaching in Africa as to take into account the current needs of the masses, their cultural and historical experiences as well as their environmental problems; but it also involves a curriculum development which makes universities and schools spearheads of larger social transformations and communal uplift in order to attain the Millenium Development Goals as well as mainstream a genuine sustainable development. In this connection, this paper makes a case for the implementation of an Afric-ecological curriculum in order to deal effectively with the multidimensional challenges of development and education in the SSA, particularly in Mali. Such a curriculum has the advantage to combine an afrocentric perspective to teaching and learning with a strong ecological awareness. In addition, it is geared toward reducing inequalities between men and women, and between rural and urban women in terms of educational and job opportunities. KEYWORDS: Development. Education. Curriculum. Afrocentricity/Africology. Educação Africo-ecológica uma estra-tégia alternativa para o desenvolvi-mento de países da África Subsaariana RESUMO O objetivo deste artigo é discutir a necessidade primordial de implementar um sistema educacional adequado, a fim de alcançar o desenvolvimento sustentável nos países da África Subsaariana (ASS), com foco em Mali, um dos países mais pobres do mundo, com uma crise endêmica educacional. É um truísmo dizer que a educação é a base do desenvolvimento. A este respeito, qualquer estratégia de desenvolvimento da ASS terá início com uma alteração na pedagogia. Essa reforma implica não apenas uma reflexão sobre a produção do conhecimento e do ensino na África como também tem em conta as necessidades atuais das massas, de suas experiências culturais e históricas, bem como seus problemas ambientais, além do envolvimento de um desenvolvimento curricular que faz com que as universidades e escolas lancem grandes transformações sociais para atingir os objetivos de desenvolvimento do milênio, bem como integrar um verdadeiro desenvolvimento sustentável. Nesse contexto, o presente trabalho faz um caso para a implementação de um currículo Africo-ecológico, a fim de lidar eficazmente com os desafios multidimensionais de desenvolvimento e de educação particularmente em Mali. Um currículo tem a vantagem de combinar uma perspectiva afrocêntrica de ensino e aprendizagem com uma forte consciência ecológica. Além disso, ele é voltado para a redução das desigualdades entre homens e mulheres e entre mulheres rurais e urbanas em termos de oportunidades de educação e trabalho. PALAVRAS-CHAVE: Desenvolvimento. Educação. Currículo. Afrocentricidade/Africologia.